Nonvital Root Canal Treatment of Necrotic Maxillary Left Lateral Incisor: A Case Report - Widyastuti, Noor Hafida; Nurhabibah, Gina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
A dental fracture or cracked tooth is a break or crack of a tooth fragment which is usually caused by traumatic injuries or attack. Traumatic injuries to the tooth can affect the pulp so that the tooth becomes necrosis (nonvital). Root treatment is one of the treatments for pulp disease by removal of the pulp from the root canal and filling the canal with obturation material. The goal is to prevent transmission of the pulp to the periapical tissue, or if it has occurred, to alter or return the periapical tissue to its normal state. This case report discusses root canal treatment of a nonvital tooth in a 31 years old female patient with fracture tooth. The treatment plan is root canal treatment which consists of three main stages that are biomechanical preparation of the root canal, root sterilization with calcium hydroxide, and obturation. Obturation of the root canal using lateral condensation technique with gutta percha material and endomethasone sealer. The success of root treatment requires knowledge of the root canal and the quality of obturation as well as the final restoration.